Korelasi parenting: perspektif psikologi dan tafsir maudhu’i surah luqmān ayat 13–17 - alfiah, nisa (Maliki Interdisciplinary Journal, 2026)
This paper examines the relationship between modern psychological parenting concepts and the educational values found in the thematic interpretation (Tafsīr Maudhū’ī) of Surah Luqmān verses 13–17. In psychology, Baumrind’s three primary parenting styles authoritarian, permissive, and authoritative significantly influence a child’s emotional, social, and cognitive development. Meanwhile, the Qur’an, through Luqmān’s counsel to his son, emphasizes the cultivation of monotheism, kindness to parents, moral awareness of the consequences of one’s actions, regular prayer, enjoining good, forbidding wrongdoing, and patience. The findings indicate that Qur’anic values align closely with the authoritative parenting style, which balances warmth, guidance, and firm boundaries. Integrating these two perspectives results in a holistic Islamic–psychological parenting model that is highly relevant to modern Muslim families. This integrated approach fosters children who are not only socially and emotionally competent but also spiritually grounded and ethically upright.